THE EFFECT OF VARIATION OF PRODUCTS AND PRICES ON CONSUMER PURCHASE DECISIONS - Syamsuri, Abd. Rasyid; Sinaga, Khairunnisa; Afrina, Yola; Ananda, Rizki Fitria; Harahap, Ayu Roma Anggito (PT Aksara Indo Rajawali, 2022)
In the Taman Bunga Dusun 5 subdistrict, Pagar Merbau District, Deli Serdang Regency, North Sumatra, this study intends to examine the impact of product variants and prices on customer purchasing decisions of decorative plants. Random sampling was utilized as the sample method. The sample size in this study is 55 people, based on the Slovin formula, which has a 10% error rate. A questionnaire was utilized to collect data. The equation Y = 6.880 + 0.606X1 + 0.447X2 was derived from the results of multiple linear regression analysis. The regression coefficient of the product variation variable (X1) obtained a t-count value of 3.666 > t-table 2.006 in the partial test (t test), indicating that product variation has a positive and significant effect on purchasing decisions with a significant value of 0.001 < 0.05 in the partial test (t test). With a significant value of 0.000 < 0.05, the regression coefficient for the price variable (X2) obtained a t-count value of 3.982 > t-table 2.006, indicating that the price has a positive and significant effect on purchase decisions. The F test revealed that the Fcount value of 49.305 > Ftable 3.18 with a significant value of 0.000<0.05, implying that product and price differences had a positive and significant impact on purchase decisions at the same time. The coefficient of determination test reveals that product variation and price variables have a 65.5 percent influence on the purchasing decision variable, with the remaining 34.5 percent influenced by variables outside of this study.